SOSIALISASI DETEKSI DINI KESEHATAN MENTAL SISWA DENGAN APLIKASI SMART SENYUM - Nawindah, Nawindah; Wulandari, Retno; Mulyati, Mulyati (Jurnal Abdi Insani, 2024)
Educational activities do not only take place in formal education but also at the Sanggar Kegiatan Belajar 27 Petukangan Selatan which is a non-formal educational institution that organizes learning activities for packages A, B and C. With various problems that occur and are experienced by students, of course, it can affect teaching and learning activities and processes. The unavailability of guidance and counseling services is one of the problems that need to be addressed by various parties, such as higher education. Special attention needs to be given, one of which is by providing early detection training for student mental health using the Smart Senyum application. The objectives of this activity are: 1) So that students can carry out early detection using the Smart Senyum application so that it can help students to find out if there are any disorders in themselves. 2) Teachers can provide the right solution to the extent of the level of mental health disorders they have. The methods of activity used are 1) Carrying out internal and external coordination. 2) Mental health socialization. 3) Training in the use of the Smart Senyum application. 4) Results. 5) Evaluation. The results of this activity were detected as students who experienced mental health disorders as many as 87% were male and 13% of students experienced mental health disorders were female. For students with a healthy mental condition, 78% of students are female. There are also 22% of male students with a healthy mental condition. The conclusion obtained is that they can understand the activities of socializing mental health with good grades and training in using the Smart Senyum application has a fairly good value. The implementation of the activity took place in an orderly manner until it was finished. With these conditions, it should be considered in making decisions related to teaching and learning activities.